Argentine Philornis Meinert species (Diptera: Muscidae) with synonymic notes - Souto Couri, Marcia (2009)
The examination of Philornis Meinert specimens recently collected in Argentina prompted this study, in which the presence of the previously recorded species is discussed and the literature concerning them is revised. From the seven species previously recorded from Argentina, we recognise three: P. torquans (Nielsen, 1913); P. blanchardi Garcia, 1952; and P. seguyi Garcia, 1952, herein considered as a senior synonym of P. nielseni Dodge, syn. nov. Philornis pici (Macquart, 1854) is considered a doubtful record and P. angustifrons (Loew, 1861) has been mistakenly recorded in Argentina. Finally, P. umanani Garcia, 1952 is considered an unrecognisable species (nomen dubium). Historical data and comments on each of these species are given.